Lefua hoffmanni Herre 1932, a junior synonym of Oreonectes platycephalus Günther 1868 (Cypriniformes: Nemacheilidae) - Ito, Taiki (Zootaxa, 2024)
Lefua hoffmanni Herre 1932 has been regarded as a valid species. However, Zheng (1989) suggested that L. hoffmanni may be a junior synonym of Oreonectes platycephalus Günther 1868. The validity of L. hoffmanni based on observations of type specimens has not been thoroughly examined in previous studies. This study comprised detailed observations and comparisons of the type specimens of L. hoffmanni and O. platycephalus to verify its validity. As a result of this investigation, it was confirmed that L. hoffmanni is indeed a junior synonym of O. platycephalus. A re-description of O. platycephalus is also provided on the basis of the syntypes.